2002
DOI: 10.1042/0264-6021:3630667
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the 1α,25-dihydroxyvitamin D3 receptor at the distal promoter region of the bone-specific osteocalcin gene requires nucleosomal remodelling

Abstract: 1alpha,25-Dihydroxyvitamin D3-mediated transcriptional control of the bone-specific osteocalcin (OC) gene requires the integration of regulatory signals at the vitamin D-responsive element (VDRE) and flanking tissue-specific sequences. The 1alpha,25-dihydroxyvitamin D3 receptor (VDR) is a member of the nuclear receptor superfamily and forms a heterodimeric complex with the receptor for 9-cis retinoic acid (RXR) that binds to the VDRE sequence. We have demonstrated previously that changes in chromatin structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 32 publications
4
29
0
Order By: Relevance
“…As VDR/RXR is unable to interact with the VDRE in ROSBRG1TA cells expressing mutant BRG1 (Fig. 8A), these results confirm previous reports indicating that a closed chromatin conformation in the OC promoter prevents interaction of the VDR complex upon vitamin D 3 stimulation (24,27).…”
Section: Binding Of Inactive Swi/snf Complexes Results In Inhibition supporting
confidence: 81%
See 1 more Smart Citation
“…As VDR/RXR is unable to interact with the VDRE in ROSBRG1TA cells expressing mutant BRG1 (Fig. 8A), these results confirm previous reports indicating that a closed chromatin conformation in the OC promoter prevents interaction of the VDR complex upon vitamin D 3 stimulation (24,27).…”
Section: Binding Of Inactive Swi/snf Complexes Results In Inhibition supporting
confidence: 81%
“…This indicates that interaction of both factors with the OC promoter is independent of SWI/SNF activity and therefore prior to the formation of the proximal DNase I-hypersensitive site. In support of this conclusion, we have previously demonstrated that Runx factors are capable of recognizing their cognate elements within the context of a nucleosomal organization (27,39) and independent of the level of core histone acetylation. 4 Together these results indicate that binding of Runx2 and C/EBP␤ is one of the early events during chromatin remodeling and transcriptional activation of the OC gene.…”
Section: Discussionsupporting
confidence: 50%
“…The retention of a nucleosome between the proximal and upstream enhancer domains reduces the distance between the basal regulatory elements and the VDRE and supports a promoter configuration that is conducive to proteinprotein interactions between VDR-associated proteins and components of the RNA polymerase II-bound complex ( Figure 2B). Interaction of the VDR at the distal promoter region of the OC gene requires nucleosomal remodeling [40,41].…”
Section: The Osteocalcin Genementioning
confidence: 99%
“…Thus, it has been reported that mutation of Runx2 sites A and B (which flank the VDRE) abolishes 1␣,25-dihydroxyvitamin D 3 enhancement of OC promoter activity (8). It was also shown, both in vitro and in intact osteoblastic cells, that VDR and Runx2 factors interact simultaneously with their cognate sequences located in close proximity within the distal region of the OC promoter (VDRE and Runx2 site B, respectively) (18,24). In addition, we have reported that in intact osteoblastic cells, the transcriptional coactivator p300 is recruited to the OC promoter by Runx2, where it up-regulates both basal and 1␣,25-dihydroxyvitamin D 3 -enhanced OC promoter activity (24).…”
mentioning
confidence: 99%